Keluarga Sakinah Dalam Perspektif Hadis Mawdhu’i - Erniati, Erniati (Pusat Studi Gender dan Anak, IAIN Palu, 2017)
Harmonious family is the ideal family, which is described as a peaceful household, harmonious and happy. Step harmonious family formation obtained information through the Koran and also refers to the hadith of the Prophet which is contained in the various books of hadith. Indicators or characteristics based on the hadith of the Prophet harmonious family who previously studied is good treatment of the spouse and other family members, each spouse and family members fulfill the duties and responsibilities in accordance with its position. Tips in building a harmonious family based on the hadith of the Prophet above is: religion is a primary gauge in selecting candidates for the couple husband and wife, each candidate has the readiness either born or inward to nurture domestic life, married for love and affection, building together in worship and build a family with devotion to Allah.